Identification of Standard Auction Models - Athey, Susan; Haile, Philip A. (Econometrica, 2002)
We present new identification resiilts for models of first-price, second-price, ascending (English), and descending (Dutch) auctions.We analyze a general specification of bidders' preferences and the underlying information structure, nesting as special cases the pure private values and pure common values models, and allowing both ex ante symmetric and asymmetric bidders.We address identification of a series of such models and propose strategies for discriminating between them on the basis of observed data.In the simplest case, the symmetric independent pri- vate values model is nonparametrically identified even if only the transaction price from each auction is observed.For more complex models, we provide conditions for identification and testing when additional information of one of the following types is available: (i) one or more bids in addition to the transaction price; (ii) exogenous variation in the number of bidders; (iii) bidder-specific covariates that shift the distribution of valuations; (iv) the ex post reahzation of the value of the object sold.Our results include new tests that distinguish between private and common values models.